2014
DOI: 10.1371/journal.pone.0112768
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Adding White Noise on Cognitive Performance of Sub-, Normal and Super-Attentive School Children

Abstract: ObjectivesNoise often has detrimental effects on performance. However, because of the phenomenon of stochastic resonance (SR), auditory white noise (WN) can alter the “signal to noise” ratio and improve performance. The Moderate Brain Arousal (MBA) model postulates different levels of internal “neural noise” in individuals with different attentional capacities. This in turn determines the particular WN level most beneficial in each individual case–with one level of WN facilitating poor attenders but hindering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 64 publications
5
61
0
1
Order By: Relevance
“…Second, previous investigations suggest that the addition of background noise can differentially influence cognitive performance of school-age children, depending on whether or not the child is attentive (Helps, Bamford, Sonuga-Barke, & Söderlund, 2014;Söderlund, Sikström, Loftesnes, & Sonuga-Barke, 2010). For example, Söderlund et al (2010) evaluated the effect of adding 78 dB background noise on children's verbal recall performance and found that performance improved with background noise for inattentive children, but decreased the performance of attentive children.…”
Section: Secondary Taskmentioning
confidence: 99%
“…Second, previous investigations suggest that the addition of background noise can differentially influence cognitive performance of school-age children, depending on whether or not the child is attentive (Helps, Bamford, Sonuga-Barke, & Söderlund, 2014;Söderlund, Sikström, Loftesnes, & Sonuga-Barke, 2010). For example, Söderlund et al (2010) evaluated the effect of adding 78 dB background noise on children's verbal recall performance and found that performance improved with background noise for inattentive children, but decreased the performance of attentive children.…”
Section: Secondary Taskmentioning
confidence: 99%
“…For instance, in children with attention deficit hyperactivity disorder (ADHD), listening to white noise has been shown to improve performance on memory 4 and go/no-go tasks 5 , as well as improve speech recognition thresholds 6 . White noise has also been shown to improve cognitive performance in typically developing school children rated as inattentive by their teachers, and worsen performance in those rated as attentive or highly attentive 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…proposed a stochastic resonance theory by alter the "signal to noise" ratio through adding different level of background white noise (Helps et al, 2014;Sderlund & Sikstrm, 2012;Söderlund, Sikström, Loftesnes, & Sonuga-Barke, 2010). It would be interesting to further compare between background speech and white noise on visual WM to extend our findings out of normal participants.…”
Section: Discussionmentioning
confidence: 73%
“…The length of these materials was edited using Adobe Audition software and restricted to 20 minutes. In addition, we set the volume of background speech and white noise to a fixed value beforehand, as previous research found it per se could modulate visual WM (Helps, Bamford, Sonuga-Barke, & Söderlund, 2014;Söderlund, Marklund, & Lacerda, 2009). To do so, we firstly used the keywords "white noise", "speech noise", "working memory" and "irrelevant speech effect" to search for relevant publications.…”
Section: Apparatus and Stimulimentioning
confidence: 99%